1998
DOI: 10.1172/jci1396
|View full text |Cite
|
Sign up to set email alerts
|

Chronic ethanol ingestion impairs alveolar type II cell glutathione homeostasis and function and predisposes to endotoxin-mediated acute edematous lung injury in rats.

Abstract: Chronic alcohol abuse increases the incidence and mortality of the acute respiratory distress syndrome (ARDS) in septic patients. To examine a potential mechanism, we hypothesized that ethanol ingestion predisposes to sepsis-mediated acute lung injury by decreasing alveolar type II cell glutathione homeostasis and function. Lungs isolated from rats fed ethanol (20% in water for >/= 3 wk), compared with lungs from control-fed rats, had greater (P < 0. 05) edematous injury (reflected by nonhydrostatic weight gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
222
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(251 citation statements)
references
References 43 publications
27
222
2
Order By: Relevance
“…Zinc also plays a role in the regulation of cellular glutathione (29) and protects cell membranes from oxidative damage (30). This is particularly intriguing, as we have published extensively on the role of oxidant stress and glutathione depletion in experimental models of chronic alcohol ingestion and in human subjects with alcohol abuse (5,7,(31)(32)(33)(34). Therefore, alcohol-induced zinc deficiency may play a central role in the oxidant stress and consequent cellular dysfunction that has been shown to characterize the alcoholic lung phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zinc also plays a role in the regulation of cellular glutathione (29) and protects cell membranes from oxidative damage (30). This is particularly intriguing, as we have published extensively on the role of oxidant stress and glutathione depletion in experimental models of chronic alcohol ingestion and in human subjects with alcohol abuse (5,7,(31)(32)(33)(34). Therefore, alcohol-induced zinc deficiency may play a central role in the oxidant stress and consequent cellular dysfunction that has been shown to characterize the alcoholic lung phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has determined that chronic alcohol ingestion in experimental animals as well as in otherwise healthy individuals has profound effects on airway epithelial and macrophage function (4)(5)(6)(7)(8)(9). Specifically, the epithelial barrier within the small gas-exchanging airways, the alveoli, is compromised.…”
Section: Abstract: Gm-csf; Phagocytosis; Tight Junctions; Zinc Transpmentioning
confidence: 99%
“…134,135 In rats, chronic feeding with ethanol reduces levels of glutathione in lung tissue, lung lavage fluid, and alveolar epithelial type II cells. 136 Chronic ethanol feeding also increased the severity of both endotoxin-induced and cecal ligation and puncture-induced lung injury. 136,137 In humans, individuals who chronically abuse alcohol but are otherwise healthy have lower levels of glutathione and a higher percentage of oxidized glutathione in bronchoalveolar lavage fluid compared with controls.…”
Section: Alcohol Abusementioning
confidence: 96%
“…136 Chronic ethanol feeding also increased the severity of both endotoxin-induced and cecal ligation and puncture-induced lung injury. 136,137 In humans, individuals who chronically abuse alcohol but are otherwise healthy have lower levels of glutathione and a higher percentage of oxidized glutathione in bronchoalveolar lavage fluid compared with controls. 138 Patients with ARDS who abuse alcohol also have decreased levels of glutathione in bronchoalveolar lavage fluid compared with normal controls.…”
Section: Alcohol Abusementioning
confidence: 96%
“…Using animal models of alcoholism, studies have shown that alcohol ingestion primes the lung for injury (18)(19)(20) and increases transforming growth factor (TGF)-b 1 in the lung (21,22). Clinically, subjects with alcoholism increased risk of acute respiratory distress syndrome after stresses, such as sepsis or trauma (23,24).…”
mentioning
confidence: 99%